Experimental and numerical research of the torsion problem of built-up steel columns laced in a single plane. (1st April 2018) - Lorkowski, Paweł; Gosowski, Bronisław
Highlights: Non-uniform torsion of steel two-chord physical single laced models. Torsion of steel two-chord numerical models laced in a single plane. Parametric analysis of steel columns subjected to uniform torsion. Uniform and non-uniform torsion stiffness of steel two chord single laced columns. Abstract: This paper presents studies carried out on physical models and numerical analyses aimed at determining the equivalent pure torsion second moment of area of built-up steel columns laced in a single plane, with the lacing located on the symmetry axis of the column cross-section. Such columns are used in overhead contact line supporting structures and in industrial halls. In order to determine the spatial stability critical loads for such columns one needs to know their pure torsion rigidity. The experimental research were carried out on single-span column models fork-restrained at their ends and subjected to a concentrated twisting moment applied at the mid-span. Among other things, the dependence between the torsion angle of the column's mid-section and the twisting moment load was determined. A similar column model was studied numerically using the finite element method and the ABAQUS software. The experimental and numerical results and the results obtained by solving a proper differential equation for the non-uniform torsion of the column, formulated in terms of the Vlasov theory, were found to be in good agreement. Also the effect of the lacing of the column with a solid web with an equivalent thickness was analysed. In addition, extensive parametric analyses of similar columns, but with a wider range of cross-sections, subjected to pure torsion were carried out using the SOFiSTiK software. The aim was to devise practical formulas for calculating the equivalent pure torsion second moment of area on the basis of the cross-section. These relations ( I T ‾ ) together with sectorial second moment of area allow to calculate the critical load capacity of spatial stability (lateral and flexural–torsional buckling) of the considered columns. Practical conclusions have been drawn.